2012
DOI: 10.3109/10799893.2012.660531
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β regulates gluconeogenic gene expression through HNF4α and FOXO1

Abstract: Hepatic gluconeogenesis is important for the maintenance of blood glucose homeostasis under fasting condition. Hepatocyte nuclear factor 4α (HNF4α) and FOXO1 transcription factors have implicated in this process through transcriptional regulation of glucose-6-phosphatase (G6Pase) and phosphoenolpyruvate carboxykinase (PEPCK), which are rate-limiting enzymes in gluconeogenesis. In this study, we demonstrate that glycogen synthase kinase 3β (GSK3β) regulates the expression of gluconeogenic genes through HNF4α an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Insulin indirectly activates PI3K, which in turn increases the activity of Akt for FoxO1 phosphorylation and leads to the exclusion of FoxO1 from the nucleus to cytosol. Gsk3, which is inactivated by Akt, has been reported to potentiate FoxO1 activity for Pepck and G6Pase expression ( 42,43 ). Our data showed that inhibiting Gsk3 activity mimicked insulin repression on GC-induced Angptl4 expression.…”
Section: Overexpression Of Foxo1 Mutant Lacking Transactivation Domaisupporting
confidence: 54%
“…Insulin indirectly activates PI3K, which in turn increases the activity of Akt for FoxO1 phosphorylation and leads to the exclusion of FoxO1 from the nucleus to cytosol. Gsk3, which is inactivated by Akt, has been reported to potentiate FoxO1 activity for Pepck and G6Pase expression ( 42,43 ). Our data showed that inhibiting Gsk3 activity mimicked insulin repression on GC-induced Angptl4 expression.…”
Section: Overexpression Of Foxo1 Mutant Lacking Transactivation Domaisupporting
confidence: 54%
“…Mechanistically, in the presence of excess amino acids, we found that upregulation of Notch1 protein levels resulted in the high expression of Rbp-Jk and Hes1 proteins, thereby enhancing FoxO1 protein levels. FoxO1 is a mediator of insulin signaling and plays an important role in maintaining glucose homeostasis (36) through transcriptional regulation of G6Pase and PEPCK, which are rate-limiting enzymes in the regulation of hepatic gluconeogenesis (43). Thus, activation of Notch1 may mediate insulin resistance in a FoxO1-dependent manner.…”
Section: Tsc2mentioning
confidence: 99%
“…After stimulation, GSK3β is released from protein anchors and is translocated to nucleus, where produces cell death (Bijur and Jope, 2001). Moreover, it has been implicated in important cellular functions achieved by GSK3 phosphorylation of numerous transcription factors (Sakamaki et al, 2012). The results described herein indicate that the toxicity of L-BMAA would imply an increase of the synthesis of GSK3β and a slight decrease of the inactive form of the enzyme.…”
Section: Discussionmentioning
confidence: 56%